Communicating Populism Comparing Actor Perceptions, Media Coverage, and Effects on Citizens in Europe - Reinemann, Carsten; Stanyer, James; Aalberg, Toril; Esser, Frank; de Vreese, Claes H. (Routledge Studies in Media, Communication, and Politics, 2019)
The studies in this volume conceptualize populism as a type of political communication and investigate it comparatively, focusing on (a) politicians' and journalists' perceptions, (b) media coverage, and (c) effects on citizens. This book presents findings from several large-scale internationally comparative empirical studies, funded by the European Cooperation in the field of Scientific and Technical Research (COST), focusing on communication and the media within the context of populism and populist political communication in Europe. The studies are based on comparative interview studies with journalists and politicians, a large-scale comparative content analysis, and a comparative cross-country experiment using nationally representative online-surveys over 15 countries. The book also includes advice for stakeholders like politicians, the media, and citizens about how to deal with the challenge of populist political communication. This enlightening volume is 'populist' in the best sense and will be an essential text for any scholar in political science, communication science, media studies, sociology and philosophy with an interest in populism and political communication. It does not assume specialist knowledge and will remain accessible and engaging to students, practitioners and policymakers.